THE IMPORTANCE OF ISLAMIC ECONOMICS IN RELIGIOUS MODERATION - Rusli Siri; Ridwan Tabe (Tasharruf: Journal Economics and Business of Islam, 2023)
Diversity can be a blessing if it is managed properly, it becomes uniqueness and strength, however, plurality can be a challenge if it is not handled wisely, it can even become a threat of division and conflict that can rip apart social security. The aim of the research was to find out the importance of Islamic economics in moderation of religion, this study used a descriptive qualitative approach with the phenomenological method, where researchers collected data with participant observation to find out the essential phenomena of participants in life experiences related to Islamic economics based on religious moderation. Sources of research data were obtained from various references which included books, journals, laws and regulations, and other relevant references. Research is carried out by collecting library data, reading, taking notes, processing research material through in-depth analysis, then making this paper a proper reading that can be used as a reference for further research. The analysis in this study uses descriptive analysis, which explains and describes the interrelationships of the Islamic economy based on religious moderation. The results of this study found that Islamic economics is important in the moderation of religion because it can create peace and tranquility in muamalah, namely mutual respect between adherents of religions is mandatory and becomes a basic foundation in everyday life. In carrying out economic activities, the concepts of Sharia will not be complete without being accompanied by religious moderation. Both Muslims and non-Muslims must be aligned in carrying out economic activities.